'A wicked problem'? Risk assessment and decision-making when licensing possession and use of firearms in Greater London. (September 2019) - Bryant, Robin; Arditti, Roger
This paper analyses the risk assessment and decision-making used by a police force to assess the suitability of a person to own a firearm. The decision to grant a firearms licence has many characteristics of a 'wicked problem'. Firearms Enquiries Officers (FEOs) in the police force concerned primarily use professional judgement to solve this problem, employing various forms of reasoning and heuristics, but potentially also prone to cognitive bias. We conclude with some observations on how training of FEOs and their supervisors in risk assessment and decision-making might be further developed.